2014
DOI: 10.1039/c3nr06323b
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid organic–inorganic heterojunction solar cells with 12% efficiency by utilizing flexible film-silicon with a hierarchical surface

Abstract: This paper reports an organic-inorganic hybrid solar cell with a hierarchical surface composed of high density silicon nanoholes and micro-desert textures. High-efficiency organic-inorganic hybrid solar cell Si/PEDOT-PSS with a hierarchical surface, showing a power conversion efficiency of 12%. The structure provides excellent light absorption over 97% for the spectral range of 300 to 1100 nm with a thickness of 60 μm due to internal multiple reflections caused by subwavelength features of high density silicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 26 publications
0
73
0
2
Order By: Relevance
“…In order to get high-power conversion efficiency hybrid solar cells, many efforts have been made to reduce the light reflection of the Si substrate. Therefore, nanostructured Si including nanowires [1], nanoholes [18], pyramids [19], and some other hierarchical structures [20] are applied to increase the light harvesting of the hybrid solar cells. Although an enhanced short-circuit current intensity (J SC ) may be obtained due to the improved light harvesting, the associated large surface/volume ratio of nanostructured Si may cause poor contact between Si and PEDOT:PSS and then serious surface recombination in the hybrid solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In order to get high-power conversion efficiency hybrid solar cells, many efforts have been made to reduce the light reflection of the Si substrate. Therefore, nanostructured Si including nanowires [1], nanoholes [18], pyramids [19], and some other hierarchical structures [20] are applied to increase the light harvesting of the hybrid solar cells. Although an enhanced short-circuit current intensity (J SC ) may be obtained due to the improved light harvesting, the associated large surface/volume ratio of nanostructured Si may cause poor contact between Si and PEDOT:PSS and then serious surface recombination in the hybrid solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…This easily causes the recombination of holes with separated electrons at the Si back surface/rear electrode interface, as discussed in the previous section. The carrier recombination is also generated via trap levels at the interface regions, as was suggested by Thiyagu et al [29]. These phenomena become active with increasing spin speeds because the increased spin speeds expand the p/n junction areas, which result in efficient carrier separation.…”
Section: Effect Of Rear Electrode Of Si/pedot:pss Hybrid Solar Cells mentioning
confidence: 71%
“…In contrast, the separated electrons at the p/n junction interface can be collected by the different processes for each rear electrode. Regarding the collection process of separated electrons, Thiyagu et al [29] reported that the holes, which are minority carriers in n-type Si, recombine with separated electrons via trap levels at the interface regions of the Si back surface/rear electrode. They also suggested that the carrier recombination at the Si back surface/rear electrode interface is suppressed by forming back-surface field (BSF) regions consisting of a heavily doped n + layer because the BSF regions act as barrier layer to prevent the ingress of holes [29].…”
Section: Effect Of Rear Electrode Of Si/pedot:pss Hybrid Solar Cells mentioning
confidence: 99%
“…[48] 图 10 TAPC 分子结构图, 器件能带图和示意图, 以及界面处 SEM 形 貌 [53] Figure 10 The molecule structures of TAPC, the device structure and cross-section SEM image of SiNW/TAPC hybrid solar cell [53] 面处理方法提高了开路电压和填充因子, 器件效率达到 了 13.01%, 是目前报道的基于硅微纳结构杂化太阳能 电池的最高效率, 说明了界面在太阳能电池中的关键性 作用. 在最近的报道中, 已经有杂化光伏器件使用超薄 的柔性硅片作为基底 [54,55] 则先将硅纳米线剥离下来, 再与 P3HT: PCBM 混合, 实 现了更好的接触优化, 将该电池的效率提升到 4.165%. 通过在硅纳米线表面用电化学的方法沉积铂的纳米颗 粒, Sun 课题组将 SiNW/P3HT 的杂化器件效率提升了 70% [60] .…”
Section: 基于硅纳米线的杂化太阳能电池unclassified
“…在 金字塔上面刻蚀硅纳米线既可以增大结区的面积(如图 12), 用短的硅纳米线就可以获得很低的反射率, 硅纳米 线长度的减少能降低表面的复合区域, 这种结构的硅和 PEDOT:PSS 杂 化 器 件 的 效 率 也 达 到 了 10% ~ 12% [27,55,66] . 采用硅纳米锥, 硅纳米管和 PEDOT:PSS 杂 化的电池效率也分别达到了 11%和 10% [25,67] .…”
Section: 基于硅纳米线的杂化太阳能电池unclassified